2002
DOI: 10.1093/brain/awf128
|View full text |Cite
|
Sign up to set email alerts
|

Dependence of subthalamic nucleus oscillations on movement and dopamine in Parkinson’s disease

Abstract: Local field potentials and pairs of neurones in the subthalamic nucleus (STN) of patients with Parkinson's disease show high-frequency oscillations (HFOs) at 15-30 Hz. This study explores how these HFOs are modulated by voluntary movements and by dopaminergic medication. We examined 15 patients undergoing implantation of bilateral deep brain stimulating electrodes using microelectrode recordings of pairs of STN neurones (eight patients) and macroelectrode recordings of local field potentials from the STN (14 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
468
3
5

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 636 publications
(538 citation statements)
references
References 75 publications
52
468
3
5
Order By: Relevance
“…86,87 Most notably in PD patients, synchronized bursting was present between the STN and the GPe, [88][89][90] in which oscillatory frequencies in the range of 15 Hz to 30 Hz (beta range) tended to predominate. 91 After dopaminergic treatment (e.g., levodopa), the power of these oscillations in the GP attenuated. 88 A similar effect in the GP was shown for clinically beneficial STN HFS parameter sets in humans.…”
Section: Regularization Of Pathological Activitymentioning
confidence: 99%
“…86,87 Most notably in PD patients, synchronized bursting was present between the STN and the GPe, [88][89][90] in which oscillatory frequencies in the range of 15 Hz to 30 Hz (beta range) tended to predominate. 91 After dopaminergic treatment (e.g., levodopa), the power of these oscillations in the GP attenuated. 88 A similar effect in the GP was shown for clinically beneficial STN HFS parameter sets in humans.…”
Section: Regularization Of Pathological Activitymentioning
confidence: 99%
“…41 There is an increase in the presence of bursts, low frequency oscillations, and synchronization in neurons in the basal ganglia and thalamus in movement disorders. 22,[42][43][44][45][46][47][48] Such changes in discharge patterns and synchronization play an important role in the pathophysiology of movement disorders. Motor symptoms including tremor, bradykinesia, and rigidity are associated with increased neuronal synchronization and low-frequency rhythmic oscillation, 49 -51 and bursts and oscillations parallel the appearance of motor symptoms in PD.…”
Section: Basal Ganglia and Thalamic Pathophysiology In Movement Disormentioning
confidence: 99%
“…Several electrophysiological studies using animal models of PD have concluded that neuronal activity patterns in the parkinsonian state show an excessive synchronized oscillatory activity in practically all parts of the corticobasal ganglia circuits (Bergman et al, 1994;Nini et al, 1995;Sharott et al, 2005;Costa et al, 2006). Similar activity patterns have also been observed in PD patients where electrophysiological recordings have been obtained in conjunction with the implantation of deep brain stimulation (DBS) electrodes (Levy et al, 2000(Levy et al, , 2002. Specifically, synchronization of neuronal activity at lower frequencies, as measured by the power of local field potential (LFP) signals in the 8-to 35-Hz frequency band, has been suggested to directly correlate with the severity of motor symptoms in PD patients (K ü hn et al, 2006).…”
Section: Introductionmentioning
confidence: 79%